The m6A reader YTHDF3 promotes TNBC progression by regulating CENPI stabilization - Zhang, Yulu; Chen, Shunji; Wu, Qiaosheng (Frontiers in Oncology, 2025)
BackgroundRNA N6-methyladenosine (m6A) readers mediate cancer progression. However, the role of eiptranscriptomic modifications such as m6A in the regulation of TNBC progression is unclear.MethodsHigh-throughput library screening identifies the key m6A regulator YTHDF3 in TNBC. Cell and animal experiments were used to identify that YTHDF3 promoted TNBC tumorigenesis to enhance Centromere protein I (CENPI) translation via m6A modification.ResultsWe showed that the N6-methyladenosine (m6A) reader YTHDF3 was an independent risk factor in TNBC and was associated with poor prognosis of patients. Notedly, overexpression YTHDF3 promoted TNBC tumorigenesis in an m6A modification, while TNBC knockdown markedly inhibited proliferation and migratory ability of tumor cells in vitro and in vivo. Mechanistically, Mechanistically, YTHDF3 interacted with Centromere protein I (CENPI) mRNAs to prolong stability of m6A-modified RNA.ConclusionOur findings indicated that m6A reader YTHDF3 contributed to tumorigenesis and poor prognosis, providing a potential prognostic biomarker and therapeutic target for TNBC.